What makes firms embrace risks? A risk-taking capability perspective - Hsiu-Fen Tsai; Chin-Jung Luan (BRQ Business Research Quarterly, 2016)
We adopt a risk-taking capability perspective to study the determinants of risk-taking behavior. We introduce the concept of “risk-taking capabilities”—absorptive capacity, network resources, and organizational slacks—arguing that recognition of threat and risk-taking capabilities will influence risk-taking behavior, while the theoretical debate on threat recognition needs to be clarified. Then, drawing from prospect theory, threat rigidity hypothesis, and resource-based views of firms (RBV), we hypothesize that firms' performance, risk-taking capabilities, and their interaction will positively correlate with risk-taking behavior. We test our hypotheses using the data from Taiwan's high technology industries. Our analyses lend support to the threat rigidity hypothesis, and risk-taking capabilities are indeed positively correlated with firms' risk-taking behavior and also moderate the relationship between past performance and risk-taking behavior."
Keywords: 650; Risk-taking behavior; Risk-taking capabilities; Prospect theory; Threat rigidity hypothesis